Inducible T cell kinase regulates the acquisition of cytolytic capacity and degranulation in CD8(+) cytotoxic T lymphocytes() - Kapnick, Senta M. (J Immunol, 2017)
Patients with mutations in ITK are susceptible to viral infections, particularly Epstein Barr Virus, suggesting that these patients have defective function of CD8(+) cytolytic T lymphocytes (CTLs). Here, we evaluated the effects of ITK-deficiency on cytolysis in murine CTLs deficient in ITK, and both human and murine cells treated with an ITK inhibitor. We find that ITK-deficiency leads to a global defect in the cytolysis of multiple targets. The absence of ITK both affected CTL expansion and delayed the expression of cytolytic effectors during activation. Furthermore, absence of ITK led to a previously unappreciated intrinsic defect in degranulation. Nonetheless, these defects could be overcome by early or prolonged exposure to IL-2, or by addition of IL-12 to cultures, revealing that cytokine signaling could restore the acquisition of effector function in ITK-deficient CD8(+) T cells. Our results provide new insight into the effect of ITK and suboptimal TCR signaling on CD8(+) T cell function, and how these may contribute to phenotypes associated with ITK-deficiency.